2013
DOI: 10.1097/pas.0b013e318283ce4c
|View full text |Cite
|
Sign up to set email alerts
|

Distinctive Histopathologic Findings of Pancreatic Hamartomas Suggesting Their “Hamartomatous” Nature

Abstract: Pancreatic hamartoma is a rare tumor, and its characteristic histopathologic features have not yet been fully evaluated. In this study, we collected 9 cases of pancreatic hamartoma to elucidate distinctive histopathologic features that can serve to establish this tumor as a clear disease entity and thus formulate useful histopathologic criteria for this tumor. The cases comprised 4 men and 5 women with a mean age of 62.7 years. The average tumor diameter was 3.3 cm. All patients underwent surgical treatment, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 4 publications
2
40
1
1
Order By: Relevance
“…However, by contrast, pancreatic GIST were numerous, as 32 cases have been reported (20)(21)(22). There were no diagnoses of leiomyosarcoma, Ewing sarcoma, liposarcoma, cavernous hemangioma, hamartoma or angiomyolipoma in the present study, in agreement with previous studies (3,8,9,(13)(14)(15)(16). Therefore, the true prevalence of the primary mesenchymal tumor types in the pancreas requires additional comprehensive studies to be elucidated.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…However, by contrast, pancreatic GIST were numerous, as 32 cases have been reported (20)(21)(22). There were no diagnoses of leiomyosarcoma, Ewing sarcoma, liposarcoma, cavernous hemangioma, hamartoma or angiomyolipoma in the present study, in agreement with previous studies (3,8,9,(13)(14)(15)(16). Therefore, the true prevalence of the primary mesenchymal tumor types in the pancreas requires additional comprehensive studies to be elucidated.…”
Section: Discussionsupporting
confidence: 82%
“…According to these previously reported studies, the most common benign tumor was schwannoma, and the most frequently reported primary sarcoma was leiomyosarcoma (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The two comprehensive studies of primary mesenchymal tumors of the pancreas performed by Kim et al (3) and the present study identified certain different results.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Well-formed islets of Langerhans are not common. In fact, Pauser et al 118, 120 and Yamaguchi et al 121 defined the criteria for the diagnosis of pancreatic hamartoma as: (1) forming a well-demarcated mass, (2) being comprised of mature acini and ducts with distorted architecture, and (3) lacking discrete islets of Langerhans. Adjacent pancreatic parenchyma is usually unremarkable.…”
Section: Pancreatic Hamartomamentioning
confidence: 99%